Two Hypotheses About Climate Change and Species Distributions - John M. Drake; John P. Wares; James E. Byers; Jill T. Anderson (Ecology Letters, 2025)
Species' distributions are changing around the planet as a result of global climate change. Most research has focused on shifts in mean climate conditions, leaving the effects of increased environmental variability comparatively underexplored. This paper proposes two new macroecological hypotheses—the variability damping hypothesis and the variability adaptation hypothesis —to understand how ecological dynamics and evolutionary history could influence biogeographic patterns being forced by contemporary large‐scale climate change across all major ecosystems. The variability damping hypothesis predicts that distributions of species living in deep water environments will be least affected by increasing climate‐driven temperature variability compared with species in nearshore, intertidal and terrestrial environments. The variability adaptation hypothesis predicts the opposite. Where available, we discuss how the existing evidence aligns with these hypotheses and propose ways in which they may be empirically tested.